2020
DOI: 10.3390/agronomy10111669
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression in 1-Methylcyclopropene (1-MCP) Treated Tomatoes during Pre-Climacteric Ripening Suggests Shared Regulation of Methionine Biosynthesis, Ethylene Production and Respiration

Abstract: The physiology of fruit ripening is defined as either ‘climacteric’ or ‘non-climacteric’. In climacteric fruit respiration during ripening increases until it reaches a peak, which is accompanied by an increase in autocatalytic ethylene production, whereas the respiration of non-climacteric fruit does not increase and they have no requirement for ethylene to complete their ripening. In an attempt to gain further insight into the involvement of autocatalytic ethylene production with the climacteric rise in respi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…In recent studies, 1-MCP has been applied to "Kinnow" mandarin , plums (Larrigaudière et al, 2009), banana (Zhu et al, 2015), tomato (Gamrasni et al, 2020), kiwifruit (Deng et al, 2013), pear (Mahajan et al, 2010), and blueberry (Chiabrando & Giacalone, 2011). However, 1-MCP can negatively impact volatile biosynthesis.…”
Section: Introductionmentioning
confidence: 99%
“…In recent studies, 1-MCP has been applied to "Kinnow" mandarin , plums (Larrigaudière et al, 2009), banana (Zhu et al, 2015), tomato (Gamrasni et al, 2020), kiwifruit (Deng et al, 2013), pear (Mahajan et al, 2010), and blueberry (Chiabrando & Giacalone, 2011). However, 1-MCP can negatively impact volatile biosynthesis.…”
Section: Introductionmentioning
confidence: 99%
“…On a broader aspect, amino acid metabolism pathways are essential for the survival of organisms because it coined itself as the building block for proteins and enzymes. In OA G20, from the interaction network, we observed that cystathionine beta-lyase (dde_0726) was enriched, which catalyzes the production of homocysteine, a direct precursor metabolite for the formation of methionine ( Gamrasni et al, 2020 ). Parallelly, methionine synthase (dde_2115) was also enriched, which is a vital enzyme in the intermediate step of methionine synthesis ( Ekstrom et al, 2003 ).…”
Section: Resultsmentioning
confidence: 99%
“…Among these antioxidant enzymes, SOD is a natural superoxide radical scavenging enzyme in cells that can convert unstable O 2− into H 2 O 2 , and POD can convert the H 2 O 2 produced by the SOD disproportionation reaction into non-toxic H 2 O [32]. Moreover, H 2 O 2 is an intermediate in the pathway of ethylene synthesis from methionine, and O 2− is related to the activity of ethylene synthase; hence, CoCl 2 may affect the production of endogenous ethylene by regulating the production of ROS in response to the P-stress conditions of fir [33]. Therefore, CoCl 2 plays an important role in the remodeling of plant roots, thereby prompting plants to respond to the P starvation environment and improving the seedlings' tolerance to P-deficient conditions.…”
Section: Discussionmentioning
confidence: 99%